NUMERICAL SIMULATION OF FOG OCCURRENCES OVER A SOUTHERN PART OF NIGERIA. - Elijah Adesanya ADEFISAN & Ezekiel YUSUF (International Journal of Research Science and Management, 2018)
Numerical prediction of fog evolution remains difficult due to its complex processes that requires adequate representation of the local perturbations in weather models despite the progress made in advance weather prediction models. The performance and sensitivity of the Weather Research and Forecasting (WRF) model in reproducing fog episodes over Akwa Ibom international airport (AKIA) Nigeria for the first time in West Africa was studied. Some real cases of radiation fog over AKIA were simulated using a set of parameterization schemes to simulate warm fog and visibility limits. Seven fog events were selected for model validation and sensitivity studies in this research work. The use of Kunkel (1984) empirical relationship result showed good agreement between simulated horizontal visibility limits using Liquid Water Content (LWC) when compared with observation. The modelled diurnal patterns of temperature, relative humidity and wind speed were also evaluated with the observed. It was found out that the model also captures the diurnal pattern and the value with very slight biases. These slight biases however, do not affect model results except where overestimation of wind speed and temperature could give rise to an earlier dissipation of fog. Fog estimation through temperature and relative humidity profile is as a result of the turbulent mixing within fog that causes the homogenization of the layers where the fog is present. The result showed evolution of fog through quasi-saturated state between temperature and relative humidity defining fog characteristic onset pronounced by surface inversion